-2a+(a+2)-3a=-7

Simple and best practice solution for -2a+(a+2)-3a=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+(a+2)-3a=-7 equation:



-2a+(a+2)-3a=-7
We move all terms to the left:
-2a+(a+2)-3a-(-7)=0
We add all the numbers together, and all the variables
-5a+(a+2)+7=0
We get rid of parentheses
-5a+a+2+7=0
We add all the numbers together, and all the variables
-4a+9=0
We move all terms containing a to the left, all other terms to the right
-4a=-9
a=-9/-4
a=2+1/4

See similar equations:

| 6-y=6-y | | Y=-2.5x+34*30 | | -4(-2+5)=29-x-9)-4x | | 3a+6=a+14 | | -4(-2)+5)=29-x-9)-4x | | -4(2(-1)+5)=29-x-9)-4x | | Y=-2.4x+140 | | 5y+7=12y | | -5=3+2a-(2a+1)+3a | | 6x-5=2x=8 | | 3x(x-4)^2x+(x-4)^3=0 | | 14.7+x2x=113.4 | | (2-y)(5y-4)=0 | | 113.4=2x+14.7+x | | 10(n+4)=90 | | 1/4p-8=10 | | 3m+5m-128=8 | | -a+2(a-2)-2a=7+2a | | 6z=$28.80 | | -x+10(1/4)=2 | | 2x3+8x2+6x−4=0 | | -4(2y+5)=2(-3-9)-4(-3) | | -7/5y=14/5 | | -(2x-1)=2(x-1) | | 3x+4(-14)=45 | | 0.08=x-0.4x | | 1/2|x-4|-5=8 | | x-46=113-46 | | x+.45x=499 | | 3(x-1)=4(x+7) | | 5(x-3)-2x-(9x-5)=8x-9x | | 15.7h+0.1=12.66 |

Equations solver categories